2009
DOI: 10.1007/s11121-009-0149-6
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Recruiting Men of Color Who Have Sex with Men in Prevention-for-Positives Interventions

Abstract: Men who have sex with men (MSM), especially MSM of color, are disproportionately impacted by HIV/AIDS compared to heterosexuals and Caucasians. Nonetheless, fewer sexual and ethnic minorities participate in prevention interventions for people with HIV. We consider recruitment for Positive Connections, a randomized controlled trial comparing unsafe sex prevention interventions primarily for HIV-positive (HIV+) MSM in six US epicenters. One community-based organization (CBO) in each city recruited adult MSM, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Researchers have identified MSM as “invisible” and “hard-to-reach” populations such that traditional probability methods of sampling (e.g., random-digit dialing) are cost-prohibitive or otherwise ineffective [3134]. Instead, researchers have employed other approaches for sampling MSM, including time–space sampling and targeted sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have identified MSM as “invisible” and “hard-to-reach” populations such that traditional probability methods of sampling (e.g., random-digit dialing) are cost-prohibitive or otherwise ineffective [3134]. Instead, researchers have employed other approaches for sampling MSM, including time–space sampling and targeted sampling.…”
Section: Discussionmentioning
confidence: 99%
“…A recent behavioral intervention study of smokers by Collins and colleagues [56] examined the relationship between recruitment methods and retention and found the likelihood of retention was five times greater if participants were recruited with a combination of proactive and reactive strategies rather than reactive recruitment alone. Results from Positive Connections, a randomized controlled trial comparing unsafe sex prevention interventions primarily for HIV-positive (HIV+) Men-who-have-sex-with-Men in six U.S. epicenters indicated that retention rates did not differ by serostatus, race/ethnicity, or recruitment method [57].…”
Section: Retentionmentioning
confidence: 99%
“…To be relevant, HIV behavioral surveillance, prevention work, and research must adequately represent those subgroups of MSM at greatest risk of infection (Halkitis, Wolitski, & Millett, 2013; Hatfield et al, 2010; McKellar, Valleroy, Karon, Lemp, & Janssen, 2006). Reflecting this need, one of the objectives of the National HIV/AIDS Strategy included the intensification of HIV prevention efforts among the groups where HIV is most heavily concentrated (CDC, 2011; White House Office of National AIDS Policy, 2010).…”
mentioning
confidence: 99%
“…Black MSM have the highest HIV prevalence and incidence rates among MSM in the U.S. (CDC, 2012b; Hatfield et al, 2010; Millett & Peterson, 2007; Prejean et al, 2011). Similarly, disproportionate rates of HIV/AIDS cases occur among Hispanic/Latino MSM (Bedoya et al, 2012; CDC, 2012b; Fernández et al, 2007; Fisher et al, 2011).…”
mentioning
confidence: 99%